Detecting Chlamydia trachomatis in men with urethritis: serology v isolation in cell culture. Issue 3 (June 1989) - Hagay, Z J; Sarov, B; Sachs, J; Shaked, O; Sarov, I
Abstract : The accuracy of single serovar (L2) inclusion immunoperoxidase assay (IPA) to show serum IgG and IgA antibodies specific to chlamydiae was compared with culture for Chlamydia trachomatis to diagnose chlamydial infection in 73 men with acute urethritis. C trachomatis only was isolated from 18 (25%), Neisseria gonorrhoeae only from 17 (23%), and both organisms from six (8%). Thus 24 (33%) yielded chlamydiae. Assays based on IgG antibodies to chlamydiae at a titre of 1/64 or more showed high sensitivity (96%) and a good negative predictive value (80%), but low specificity (13%) and agreement (48%) compared with culture. IgG antibodies to chlamydiae at a titre of 1/128 or more showed lower sensitivity (75%) but higher specificity (72%), negative predictive value (79%), and agreement (73%). IgA antibodies to chlamydiae at a titre of 1/8 or more showed a sensitivity of 88%, specificity of 72%, negative predictive value of 88%, and agreement of 79%. An appreciable (fourfold or more) decrease in IgA and IgG titres was observed in most (10) of the 15 men from whom second blood samples were obtained one to two years after treatment. Measuring specific IgA and IgG antibodies to chlamydiae by IPA may serve as a useful complementary test for diagnosing and following up patients with urethritis.